2014
DOI: 10.1017/s0960258514000087
|View full text |Cite
|
Sign up to set email alerts
|

Physical dormancy in Senna multijuga (Fabaceae: Caesalpinioideae) seeds: the role of seed structures in water uptake

Abstract: Structural studies in seeds with physical dormancy (PY) are important to better understand its causes and release when subjected to treatments for dormancy breaking. The aims of this study were to (1) characterize the PY break; (2) examine the role of different seed structures in water uptake; and (3) identify the water gap in Senna multijuga seeds. Imbibition patterns of dormant and non-dormant (subjected to dormancy breaking treatments) seeds and the morphological changes during dormancy breaking and germina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
(68 reference statements)
2
35
0
1
Order By: Relevance
“…The thickness of this layer decreases considerably at the lens, as also reported for D. illinoensis (Olszewski et al, 2013) and several species of Mimosoideae and Papilionoideae (Dell, 1980;Rodrigues-Junior, Faria, Vaz, Nakamura, & José, 2014;Serrato-Valenti et al, 1995). This indicates that the lens area is physically the weakest part of the seed coat, and thus, most prone to breakage during different treatments (Baskin et al, 2000;Hu et al, 2009;Rodrigues-Junior et al, 2014;Serrato-Valenti et al, 1995;Ventura de Souza, Voltolini, Santos, & Paulilo, 2012 However, in the present work, the thickness of this layer at the lens was very variable and depended on a greater number of variables that was the case for the sector opposite to the lens. This could indicate that the thickness of this layer behind the lens is more sensitive to the maternal environment when compared to its opposite sector, indicating a greater phenotypic plasticity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The thickness of this layer decreases considerably at the lens, as also reported for D. illinoensis (Olszewski et al, 2013) and several species of Mimosoideae and Papilionoideae (Dell, 1980;Rodrigues-Junior, Faria, Vaz, Nakamura, & José, 2014;Serrato-Valenti et al, 1995). This indicates that the lens area is physically the weakest part of the seed coat, and thus, most prone to breakage during different treatments (Baskin et al, 2000;Hu et al, 2009;Rodrigues-Junior et al, 2014;Serrato-Valenti et al, 1995;Ventura de Souza, Voltolini, Santos, & Paulilo, 2012 However, in the present work, the thickness of this layer at the lens was very variable and depended on a greater number of variables that was the case for the sector opposite to the lens. This could indicate that the thickness of this layer behind the lens is more sensitive to the maternal environment when compared to its opposite sector, indicating a greater phenotypic plasticity.…”
Section: Discussionsupporting
confidence: 78%
“…However Hopkinson and English (2004) reported that tears could occasionally occur in the testas of immature seeds due to the stresses associated with buckling of the embryo during drying, and these then could become points of first water entry. Hu et al (2009) reported that seeds may respond differently to different types of dormancy-breaking treatments, which could result in water uptake through different sites (Rodrigues-Junior et al, 2014). These possibilities should be considered in future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the low germination percentage can be attributed to a possible physical dormancy. Several papers have been reported physical dormancy in seeds of the Senna genus, for example, Senna macranthera (POZITANO e ROCHA, 2011), Senna Silvestris (MARANHO and PAIVA, 2012), Senna multijuga (RODRIGUES-JUNIOR et al, 2014), among others. Jayasuriya et al (2013) studying 100 Fabaceae species from Sri Lanka, found 94 presenting orthodox behaviour, of those 91 presented some kind of dormancy and 86 presented physical dormancy.…”
Section: Figurementioning
confidence: 99%
“…) and physically dormant (Rodrigues‐Junior et al . ) seeds. For dormancy to be broken naturally in S. multijuga seeds, an opening needs to be formed in the lens, which acts as a water gap (Rodrigues‐Junior et al .…”
Section: Introductionmentioning
confidence: 99%